THE PRESENCE OF PROTEIN A ON THE SURFACE OF STAPHYLOCOCCUS AUREUS BACTERIAL CELLS USING SERUM SOFT AGAR TECHNIQUES - Djannatun, Titiek (Lembaga Penelitian Universitas YARSI, 2016)
Protein A is a specific proteins on the surface of some Staphylococcus aureus (S. aureus) strains. Staphylococcus bacteria which have protein A has widely used in the biomedical. Aims of this study to find a simple method of detecting the presence of S. aureus protein A. 15 S. aureus isolates from field cases, S. aureus cowan I as positive control, Staphylococcus epidermidis dan Micrococcus sp as negatif control were used. Bacteria was inoculated into 10 ml Todd Hewith Broth medium, Soft Agar (SA) and into 10 ml of serum soft-agar (SSA), agitated using a vortex and incubated at 37oC for 18-24 h. Form of colonies that grew was observed and categorized as compact and diffuse colonies. The colonies that suspected contain protein A conducted confirmation tests by Dot Blot. 7 isolates showed the change of colony formation from diffuse to compact in SSA (SA added rabbit or chicken serum), and 8 isolates remain diffuse. Dot Blot test positive. Protein A has the ability to bind the Fc fraction of IgG but not the IgY from birds. The binding of S. aureus and IgG could be demonstrated by the change of colony growth from diffuse before the addition of serum containing IgG in SA to compact after the presence of serum. Protein A on the bacterial cell surface bind the Fc-IgG caused steric hinderance of bacteria and expressed as compact colony formation in SA. SSA using mammalian sera can be used to discriminate the bacterial strains with or without protein A.